Security-Aware Digital Twin Ecosystems for Cyber-Physical Systems: Integrating Threat Intelligence, Blockchain, And Generative AI for Resilient Industrial and Healthcare Infrastructures - Kwame Mensah (Emerging Frontiers Library for The American Journal of Interdisciplinary Innovations and Research, 2026)
Digital twin technology has emerged as a transformative paradigm in cyber-physical systems, enabling the creation of dynamic virtual representations of physical assets, industrial infrastructures, and even human biological processes. While digital twins offer significant benefits for predictive maintenance, operational optimization, and real-time system monitoring, their increasing integration with critical infrastructures introduces complex cybersecurity challenges. Industrial control systems, smart manufacturing environments, and healthcare digital twins rely heavily on interconnected networks, cloud platforms, and distributed data architectures that are vulnerable to sophisticated cyber threats. Recent cyber incidents targeting industrial environments demonstrate that adversaries increasingly exploit the operational technology layer to disrupt physical processes. Consequently, the convergence of digital twin technology with cybersecurity frameworks has become a critical research priority. This study investigates the design of security-aware digital twin ecosystems capable of supporting resilient cyber-physical infrastructures. Drawing upon interdisciplinary literature from cybersecurity, industrial automation, digital twin architectures, and artificial intelligence research, the article develops a comprehensive conceptual framework for secure digital twin environments. Particular emphasis is placed on integrating cyber threat intelligence, blockchain-based data integrity mechanisms, intrusion detection systems, and generative artificial intelligence for proactive cyber defense. The research examines how digital twins can be used not only as operational monitoring tools but also as cybersecurity instruments that simulate attack scenarios, detect anomalies in industrial processes, and support security operations centers in real-time threat analysis. The study further explores the role of distributed ledger technologies in enabling secure data sharing among digital twin networks while maintaining transparency and trust in collaborative industrial ecosystems. Additionally, the article investigates emerging applications of digital twin security architectures in healthcare systems, where human digital twins and medical digital representations require strong privacy and security protections. Through extensive theoretical analysis, the research identifies critical architectural components required for secure digital twin ecosystems, including data governance frameworks, simulation-based threat detection mechanisms, and AI-driven sensor fusion capabilities. The findings suggest that combining digital twins with blockchain infrastructures, threat intelligence analytics, and machine learning-based anomaly detection can significantly enhance the resilience of cyber-physical systems. However, the increasing complexity of these systems introduces challenges related to privacy protection, computational scalability, and regulatory governance. The article concludes by proposing a conceptual roadmap for the development of next-generation security-aware digital twin infrastructures capable of supporting both industrial and biomedical cyber-physical environments.